2018
DOI: 10.1007/s10637-018-0591-z
|View full text |Cite
|
Sign up to set email alerts
|

A phase I, open-label, two-stage study to investigate the safety, tolerability, pharmacokinetics, and pharmacodynamics of the oral AKT inhibitor GSK2141795 in patients with solid tumors

Abstract: Background We sought to determine the recommended phase II dose (RP2D) and schedule of GSK2141795, an oral pan-AKT kinase inhibitor. Patients and Methods Patients with solid tumors were enrolled in the dose-escalation phase. Pharmacokinetic (PK) analysis after a single dose (Cycle 0) informed dose escalation using accelerated dose titration. Once one grade 2 toxicity or dose-limiting toxicity was observed in Cycle 1, the accelerated dose titration was terminated and a 3 + 3 dose escalation was started. Continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
(17 reference statements)
2
24
0
1
Order By: Relevance
“…Similarly, uprosertib treatment has been shown to cause dosedependent hyperglycaemia and reduced glucose uptake in patients with gynaecological malignancies. 22,23 Glucose carbon entry into the TCA cycle via PDH was also inhibited by uprosertib, consistent with previous work that suggests a direct interaction between PDH subunit B and AKT1 and that silencing of AKT1 could reduce PDH flux from 13 C labelled glucose. 35 By contrast exogenous lactate incorporation into citrate was maintained in cells treated with uprosertib.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly, uprosertib treatment has been shown to cause dosedependent hyperglycaemia and reduced glucose uptake in patients with gynaecological malignancies. 22,23 Glucose carbon entry into the TCA cycle via PDH was also inhibited by uprosertib, consistent with previous work that suggests a direct interaction between PDH subunit B and AKT1 and that silencing of AKT1 could reduce PDH flux from 13 C labelled glucose. 35 By contrast exogenous lactate incorporation into citrate was maintained in cells treated with uprosertib.…”
Section: Discussionsupporting
confidence: 89%
“…Clinical reports indicate that uprosertib treatment as a monotherapy is primarily associated with tumour growth inhibition and stable disease at the recommended phase II dose (75 mg) in patients with solid tumours. 22 Since lactate concentrations and acidity are often elevated in the tumour microenvironment, the cytostatic response to uprosertib in the presence of lactic acid in our experimental system potentially mimics the stable disease response that has been observed in patients. Glycolysis inhibition occurred upon treatment with uprosertib in the presence and absence of lactic acid supplementation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The safety, tolerability, pharmacokinetics, and pharmacodynamics of the drug were evaluated in a phase I, open-label study in patients with solid tumors. Uprosertib was safe and well-tolerated, most treatment-related adverse events were low grade and included diarrhea, fatigue, vomiting and decreased appetite ( 160 ).…”
Section: Akt Inhibitors In Clinical Studiesmentioning
confidence: 99%
“…Similarly, clinical trials with GSK2141795 and MEK inhibitor GSK1120212 shows that 93% inhibition of tumor growth in the pancreatic cancer tumor model, which is much more effective than the drug alone. In addition, combination with Bortezomib and Dexamethasone of multiple Myeloma in the phase I clinical trial has also been completed (NCT01428492), showed an overall response rate of 41% . GSK2141795 is not in active development lately.…”
Section: Atp‐competitive Akt Inhibitorsmentioning
confidence: 99%